The great nursery rhyme disaster - Conway, David, 1970-; Williamson, Melanie (WIlton, CT : Tiger Tales, 2009)
Little Miss Muffet is bored being in the same old nursery rhyme, so she sets off to explore the other pages of the nursery rhyme book to see what the other characters are up to.
2.9
K-3
Keywords: Boredom -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Boredom -- Fiction; Characters in literature -- Fiction; Humorous stories; Boredom -- Fiction; Characters and characteristics in literature -- Fiction; Humorous fiction; Humorous fiction